Genetic Landscape of Nephropathic Cystinosis in Russian Children - Savostyanov, K. V.; Pushkov, A. A.; Shchagina, O. A.; Maltseva, V. V.; Suleymanov, E. A.; Zhanin, I. S.; Mazanova, N. N.; Fisenko, A. P.; Mishakova, P. S.; Polyakov, A. V.; Balanovska, E. V.; Zinchenko, R. A.; et al. (Frontiers in Genetics, 2022)
Nephropathic cystinosis is a rare autosomal recessive disorder characterized by amino acid cysteine accumulation and caused by biallelic mutations in the CTNS gene. Analysis methods: tandem mass spectrometry to determine the cystine concentration in polymorphonuclear blood leukocytes, Sanger sequencing for the entire coding sequence and flanking intron regions of the CTNS gene, multiplex PCR to detect a common mutation - a 57 kb deletion, Multiplex Ligation-dependent Probe Amplification to analyze the number of exon copies in the CTNS gene. Haplotype analysis of chromosomes with major mutations was carried out using microsatellite markers D17S831, D17S1798, D17S829, D17S1828, D17S1876. In this study, we provide clinical, biochemical, and molecular genetic characteristics of 40 Russian patients with mutations in the CTNS gene. 30 of these patients were selected from a high-risk group of 85 people as a result of selective screening, which was carried out via cystine concentration measurement in polymorphonuclear blood leukocytes. The most common pathogenic variant, as in most described studies to date, was the 57 kb deletion, which represented 25% of all affected alleles. Previously non-described variants represented 22.5% of alleles. Founder effect in the Karachay and Chechen ethnic groups was shown for the following major variants: c.1015G>A and c.518A>G.